Organized crime in the united kingdom - Campana, Paolo (The British journal of criminology, 2018)
This article focuses on governance-type organized crime (OC). First, it explores two cases of illegal governance in Salford (Greater Manchester) and Derbyshire by relying on a wide range of qualitative data. Next, it presents a novel instrument measuring the strength of governance-type OC, the ‘Illegal Governance (i-Gov) Index’. This instrument is then included in a survey we conducted with Derbyshire Constabulary. This is the first systematic attempt to measure such crime in the United Kingdom. The article shows that the governance dimension of OC is present in the United Kingdom, although with varying degrees of sophistication and development. While comparatively rare, this form of OC is pernicious and highly destructive of communities. This article therefore calls for a systematic evaluation of such phenomenon across the United Kingdom, based on the i-Gov Index.